1992
DOI: 10.1161/01.atv.12.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and species differences in bile salt-dependent neutral cholesteryl ester hydrolase activity and gene expression.

Abstract: Enzymatic activity and raRNA abundance for neutral bile salt-dependent cholesteryl ester hydrolase (CEH) were determined in rat and rabbit tissues. In rat liver and intestine, enzyme activity and mRNA levels varied independently. Particularly striking in most tissue samples was the absence of detectable CEH mRNA in the presence of enzymatic activity, suggesting that there was an exogenous source of enzyme. Rabbits differed from rats in four ways. First, neither CEH activity nor mRNA was present in any liver sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Species differences in tissue expression of the bile salt-stimulated cholesterol esterase gene have been reported previously (44). While the pancreas of all species examined to date were capable of cholesterol esterase biosynthesis, the bile salt-stimulated pancreatic type cholesterol esterase mRNA was present only in rabbit intestine and not the intestine of rat, human, or mouse (41,44).…”
Section: Expression Of Cholesteryl Ester Hydrolytic Enzymes In Mousementioning
confidence: 70%
See 1 more Smart Citation
“…Species differences in tissue expression of the bile salt-stimulated cholesterol esterase gene have been reported previously (44). While the pancreas of all species examined to date were capable of cholesterol esterase biosynthesis, the bile salt-stimulated pancreatic type cholesterol esterase mRNA was present only in rabbit intestine and not the intestine of rat, human, or mouse (41,44).…”
Section: Expression Of Cholesteryl Ester Hydrolytic Enzymes In Mousementioning
confidence: 70%
“…While the pancreas of all species examined to date were capable of cholesterol esterase biosynthesis, the bile salt-stimulated pancreatic type cholesterol esterase mRNA was present only in rabbit intestine and not the intestine of rat, human, or mouse (41,44). Cholesterol esterase mRNA was reported to be present in some but not all rat liver tested (41,44), and was absent in the rat hepatoma Fu5AH cells (15). However, the cholesterol esterase mRNA was detectable in the HepG2 human hepatoma cells (Ref.…”
Section: Expression Of Cholesteryl Ester Hydrolytic Enzymes In Mousementioning
confidence: 99%
“…Conversely, as one early study has shown, for certain hydrolases there is little correlation between mRNA levels and lipolytic activity. 46 It remains to be determined how epoxycholesterol decreases CE hydrolysis in lipid-loaded macrophages. We do know that this occurs independently of LXR activation, because the simultaneous treatment of lipid-loaded THP-1 cells with epoxycholesterol and an LXR antagonist does not increase cholesterol efflux, and the addition of an LXR synthetic agonist in conjunction with epoxycholesterol fails to rescue the efflux defect (supplemental Figure II) macrophages via transcriptional downregulation of CEH or HSL, the possibility of altered posttranslational regulation of these enzymes remains to be investigated, as well as the contribution of other candidate enzymes for CE hydrolysis in these macrophages.…”
mentioning
confidence: 99%
“…The function of this expression is still unknown, but it has been suggested that CEL interacts with cholesterol esters and oxidized lipoproteins and thereby modulates the progression of atherosclerosis (16,17). Furthermore, there seem to be differences with respect to the tissue-specific expression among different species (18). This might be explained by differences that have taken place during the evolution of the CEL gene locus.…”
mentioning
confidence: 99%